1999
DOI: 10.1038/sj.bjc.6690145
|View full text |Cite
|
Sign up to set email alerts
|

Time at surgery during menstrual cycle and menopause affects pS2 but not cathepsin D levels in breast cancer

Abstract: Many studies have addressed the clinical value of pS2 as a marker of hormone responsiveness and of cathepsin D (Cath D) as a prognostic factor in breast cancer. Because pS2 and Cath D are both oestrogen induced in human breast cancer cell lines, we studied the influence of the menstrual cycle phase and menopausal status at the time of surgery on the levels of these proteins in breast cancer. A population of 1750 patients with breast cancer, including 339 women in menstrual cycle, was analysed. Tumoral Cath D a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…Our finding that high TFF1 levels were related to premenopausal patients is in accordance with the findings of other studies 21, 41, although some opposite findings were also reported 32. Considering that middle-aged group (45-59 years old) consisted of both premenopausal and postmenopausal patients while all patients younger than 45 were premenopausal and all patients older than 59 were postmenopausal in our study, age of the patients was not analyzed as a continuous variable, but stratified into three age subgroups.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that high TFF1 levels were related to premenopausal patients is in accordance with the findings of other studies 21, 41, although some opposite findings were also reported 32. Considering that middle-aged group (45-59 years old) consisted of both premenopausal and postmenopausal patients while all patients younger than 45 were premenopausal and all patients older than 59 were postmenopausal in our study, age of the patients was not analyzed as a continuous variable, but stratified into three age subgroups.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it has also been reported that there is a highly significant correlation between the expression of TFF1 by primary tumors and their metastases [15], suggesting that this expression is constant along the tumoral progression. Other interesting finding in the present study has been the presence of higher TFF1 tumoral levels in premenopausal women than in postmenopausal ones, which has also been described in a prior study [16]. Considering that TFF1 is an estrogen-induced protein, this finding might suggest a possible influence of serum estrogen levels on the production of TFF1 by tumors.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, the observation of lower levels of pS2 in the older group could be justified by the fact that pS2-positive protein status has only been associated with ER-positive status in patients aged 50 years or less [ 51 ]. Indeed, previous studies showed that tumour pS2 concentration tends to be lower in postmenopausal patients [ 52 , 53 ], whereas cathepsin D tumour level does not show significant variation between pre- and postmenopausal patients [ 53 ]. The agreement between the literature evidence and the present study’s findings reinforces the capability of HAC in identifying strongly differentiated groups.…”
Section: Discussionmentioning
confidence: 99%